Longitudinal Study of Low Serum LDL and Depressive Symptom Onset in Postmenopause - Persons, Jane E. (J Clin Psychiatry, 2016)
OBJECTIVE: The aim of this study was to characterize the relationship between serum low-density lipoprotein cholesterol (LDL-c) and subsequent depressive symptoms onset in postmenopausal women. We secondarily assessed serum high-density lipoprotein (HDL-c), total cholesterol, and triglycerides. METHODS: This population-based prospective cohort study utilizes data from 24,216 50-79 year old participants of the Women’s Health Initiative, which originally ran from 1993-2005 and has since incorporated two extension studies, with the most recent culminating in 2015. Fasting lipids were measured for all participants at baseline, and for a subset through six years of follow-up. Depressive symptoms were characterized using the Burnam eight-item scale for depressive disorders (Center for Epidemiologic Studies-Depression/Diagnostic Interview Schedule short form) at baseline and over follow-up, using a cutpoint of 0.06 to indicate presence of depressive symptoms. RESULTS: The lowest quintile of LDL-c was associated with an increased risk of subsequent depressive symptoms (HR=1.25, CI 1.05-1.49, p=0.01) and follow-up analyses demonstrated that the elevated risk appeared to be confined to the lowest decile (LDL-c <100 mg/dL). Further, this elevated risk was moderated by lipid-lowering drug treatment. Elevated risk was demonstrated among those who reported no lipid-lowering medication use (HR=1.23, CI 1.03-1.47, p=0.02), but not among those reporting use (HR=0.65, CI 0.18-2.29, p=0.50). CONCLUSION: Among postmenopausal women, untreated serum LDL-c below 100 mg/dL was associated with an increased risk of developing depressive symptoms. No excess risk was observed in those attaining LDL-c <100 mg/dl with lipid-lowering therapy. These findings have important implications for risk assessment, treatment considerations, and mechanistic insight.